Validação do diagnóstico autodeclarado de depressão em participantes da Coorte de Universidades Mineiras (Projeto CUME) - Bruna Flavia dos Santos (2020)
Introduction: Depression is an important public health problem, being globally considered to be the main cause of incapability. The prevalence of this disease, in 2015, was estimated in 4.4%, corresponding to 322 million cases all around the world. In Brazil, it is estimated that 5.8% of the population suffer from depression. Besides the incapability caused by the disease, it is associated with a greater occurrence of suicide and it is also a risk factor for the development of noncommunicable diseases. In this context, the Cohort of Universities of Minas Gerais (CUME) has, as one of its objectives, to evaluate the relationship between depression, lifestyle and chronic health outcomes in federal university graduates in the state of Minas Gerais. However, the depression diagnoses have been selfdeclared by the participants, making it necessary to be validated in order to increase the quality of the scientific evidences produced by that project. Objective: To validate the self-declared diagnoses of depression given by participants in the CUME project. Methods: In this cross-sectional study, were included 79 participants who answered to the project’s follow-up questionnaire, between March and August of 2018 (43 with and 36 without self-report depression). A team of four psychiatrists applied the DSM5, using the structured clinical interview for mental disorders (SCID-5-CV) as a reference, during appointments in person with the participants between October and November of 2019. The percentage of agreement, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) have been calculated between the self-reported depression diagnoses and those confirmed by the psychiatrists, besides the Kappa test application. The percentage of false positives and false negatives produced by the self-reported diagnoses in relation to those given by the psychiatrists has also been calculated. Results: The majority of the participants were female (82.3%), young adult (60.8% between 20 and 39 years of age), with no common-law marriage (54%), with postgraduate studies (75.9%) and currently employed (72.2%), non-smokers (69.6%), sedentary/insufficiently physically active (69.6%). In addition, high proportions of participants reported binge drinking (36.7%) and inadequate ingestion of carbohydrates (50.6%) and lipids (78.5%). There were no statistical differences for variables according to self-report of depression or non-depression. The agreement between the diagnose of depression was 81.0% with sensitivity of 80.6%, specificity of 81.4%, PPV of 78,4%, NPV of 83,3% and Kappa value of 0.62. Additionally, 18.6% and 19.4% of false positive and false negative were observed, respectively. Conclusion: The depression diagnoses self-declared by the participants of the CUME project presents good accuracy, being valid for utilization in studies about this health outcome in this population.